The Effectiveness of Grow Model Coaching to Improve Adaptive Performance in the Community in the Maritime Village Area of the TNI-AL Archipelago - Jannah, Nur; Bantam, Dian Juliarti (International Journal of Science and Society, 2023)
Kampung Bahari Nusantara (KBN) is one of the coastal areas developed in collaboration with the Indonesian Navy. The Nusantara Maritime Village program has spread in various parts of Indonesia, one of which is in Trisik Sidorejo Hamlet, Banaran Village, Galur District, Kulon Progo, Yogyakarta Special Region. Nusantara Maritime Village has valuable and varied objectives, including cultural preservation, education, tourism, and environmental preservation. Trisik Sidorejo Hamlet is a TNI-AL assisted area that has a population of approximately 600 people with 222 family cards. The TNI-AL assisted community has its own uniqueness compared to other areas, the TNI-AL assisted community pursues two professions at once, namely fishermen and farmers. With this uniqueness, the TNI-AL assisted community needs to continue to have good performance and adaptation processes, so that they can realize their hopes and goals when working. The purpose of this study is to determine the effectiveness of the grow model coaching to improve adaptive performance in the community in the TNI-AL archipelago maritime village area. The subjects in this study were TNI-AL fostered communities in the trisik sidorejo hamlet. The analysis method in this study uses a non-parametric test, non-parametric analysis is a data analysis that uses a static test whose model does not determine the existence of certain conditions about population parameters. Thus, non-parametric statistics do not require data to be normally distributed, the general scale is nominal and ordinal, the sample may be small (Slegal, 1997).